Development of Quality Culture at Madrasah Tsanawiyah Negeri 1 Kebumen through Full-Day School Classes - Salim Wazdy; Fauzi Fauzi (Universitas Muhammadiyah Ponorogo, 2023)
MTs Negeri 1 Kebumen has done developing be a quality culture through Full Day School classes. The results can be seen with various academic and non-academic achievements up to the National level. Graduates of MTs Negeri 1 Kebumen are free to choose their favorite school. Until now, graduates of MTs Negeri 1 Kebumen are still the biggest contributors to MAN IC Serpong and MAN IC Pekalongan. The community also gives appreciation by scrambling to get into MTs Negeri 1 Kebumen , it can be seen that every year the average number of registrants is twice what is needed. This study focuses on developing a quality culture at MTs Negeri 1 Kebumen through full day school classes, the influencing factors and their implications. This research is a qualitative research with an ethnographic approach. The results of the research on the development of a quality culture through full day schooling, started in 2007, and began to show results in 2012. The development of a quality culture through a system work with a structured organization under the head of the madrasa. The quality culture values developed are a culture of discipline, a culture of independent learning, a culture of achievement, a religious culture, a literacy culture, a culture of evaluation and reflection for improvement, a culture of complementing facilities and a culture of teachers compiling learning tools.